Politeness Principles Of Flouting Maxims Used By The Characters Of “The School Of Rock” Movie - Steffanie Amalia (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
The primary objective of this research is to examine and analyze the several instances in which the characters in the movie entitled "The School of Rock" flouted politeness maxims. Additionally, this research aimed to ascertain the underlying motivations of the characters in flouting the maxims, based on the context of situation. The documentation method was applied in this research to gather data that was methodically observed and documented. Due to its reliance on narrative description and without any numerical form, this research applied a descriptive qualitative methodology. The data, which was collected and consisted of utterances that violated maxims, was examined using several techniques. Based on the analysis, 23 data were found. 1 data of flouting generosity maxim, 12 data of flouting approbation maxim, 1 data of flouting modesty maxim, 4 data of flouting agreement maxim, 3 data of flouting sympathy maxim, which means the characters flouted all types of politeness principles maxims. The analysis of characters flouting maxims indicates that the motivations behind their actions vary depending on the context of situation. Most of the situations based on the context in the movie is dispraising to others, because of this, the characters mostly flouted approbation maxim.